NMR and MRI observation of water absorption/uptake in hemp shives used for hemp concrete. (15th October 2016) - Fourmentin, M.; Faure, P.; Pelupessy, P.; Sarou-Kanian, V.; Peter, U.; Lesueur, D.; Rodts, S.; Daviller, D.; Coussot, P.
Highlights: Distribution of NMR relaxation time allows to quantify water transfers in hemp. Water absorption in hemp occurs in two steps of very different characteristic times. Such a measure is better controlled than usual standard weighing techniques. Abstract: Hemp concrete used as a construction material is known to provide excellent thermal insulation and hydric regulation, and prevents condensation. Initial water content in the hemp and water exchanges between hemp and binder play a major role in these processes. Here we study how hemp absorbs liquid water. In that aim we rely on 1 H NMR (Nuclear Magnetic Resonance) measurements which make it possible to distinguish water situated inside from water situated outside the hemp. Then, following the evolution of the distribution of NMR relaxation times we are able to quantify the effective amount of water entering the hemp as a function of time. We show that such a measure is better controlled than usual techniques such as weighing an immersed sample or the TC (Technical Committee) RILEM (Réunion Internationale des Laboratoires et Experts des Matériaux, systèmes de construction et ouvrages) method which cannot easily distinguish water inside hemp from water situated outside or wetting the external hemp surface. The water absorption in hemp occurs in two steps: about half the water enters the material in a time of the order of a minute, while the second half of water slowly penetrates over a time of the order of three days. Finally, from 1 H micro NMR imaging we show that the first step corresponds to water entering the pith while the second one corresponds to water diffusing in the wood part of the shiv.